Collaborative Governance In Improving Population Income Through The Potential Of Agricultural Sector Business In Tanjung Jabung Barat District, Jambi Province - Yogi Mei Saputra; Muhadam Labolo; Baharuddin Thahir (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the implementation of Collaborative Governance using the Penta Helix model in increasing community income through the potential of the palm oil agricultural sector in Tanjung Jabung Barat Regency. The research employs a qualitative descriptive method with data collected through interviews, observations, and documentation involving various actors namely the local government, academia, business sector, community, and media. The findings indicate that the implementation of Collaborative Governance in Tanjung Jabung Barat has progressed through the synergy among actors in programs such as DBH Sawit , farmer training, and partnerships with the private sector, although challenges remain in terms of farmers' capacity, bureaucracy, and inter-agency coordination. The local government seeks to overcome these barriers by strengthening cross-sector communication, empowering farmer groups, and encouraging active participation from all elements of the Penta Helix. The study concludes that the improvement of palm oil farmers' income depends on the consistency and sustainability of collaborative synergy.